Microwave radar imaging of inhomogeneous breast phantoms using circular holography - Flores-Tapia, Daniel; Maizlish, Oleksandr; Alabaster, Clive M.; Pistorius, Stephen (Cranfield University, 2012)
Circular holography is a novel reconstruction technique for Breast Microwave Radar (BMR) imaging. Compared to current state of the art BMR image formation methods, this reconstruction approach yields spatially accurate images with higher signal to noise ratios and no artifacts. Nevertheless, a preclinical study is required to assess the feasibility of this technique in realistic breast imaging scenarios. In this paper, a series of preliminary results showing the performance of circular holography on preclinical datasets are presented. These datasets were recorded from inhomogeneous breast phantoms that mimic the dielectric properties and the anatomy of the different breast tissues. These phantoms were fabricated using Magnetic Resonance (MR) images a base model to emulate the shape and volumes of dense tissue regions. The reconstructed BMR images show that tumor and fibroglandular tissue responses can be effectively distinguished, suggesting that circular holography can be used as BMR reconstruction approach in clinical scenarios.
Keywords: Image reconstruction; Tumors; Breast; Phantoms; Dielectrics; Radar imaging; Signal to noise ratio; Preclinical feasibility; Breast microwave radar; Image reconstruction